2014
DOI: 10.1175/jtech-d-13-00105.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wind Guess on the Tracking of Atmospheric Motion Vectors

Abstract: The goal of this paper is to show the impact of the use of the wind guess (WG) in atmospheric motion vector (AMV) extraction schemes. The study has been performed using the Satellite Application Facility on Support to Nowcasting and Very Short Range The results show an impact on the amount of valid AMVs extracted by each configuration. Not using the wind guess produces more valid AMVs when large target boxes and short temporal gaps are used. It is the opposite when small target boxes and long temporal gaps are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…This means that it is difficult to track the target when the target box sizes are excessively small or large. These results are in good agreement with those reported in previous research [19,20,38]. However, the validation scores with AMVs of QIF > 80 were almost independent of the target box size regardless of the channel.…”
Section: Validation and Optimization Of The Gk-2a Amv Algorithmsupporting
confidence: 92%
“…This means that it is difficult to track the target when the target box sizes are excessively small or large. These results are in good agreement with those reported in previous research [19,20,38]. However, the validation scores with AMVs of QIF > 80 were almost independent of the target box size regardless of the channel.…”
Section: Validation and Optimization Of The Gk-2a Amv Algorithmsupporting
confidence: 92%
“…It reduces computing time drastically and improves the robustness of AMV tracking. The impacts of the use of the guess are explained by Borde et Garcia Pereda [10]. The forecasted wind is retrieved at the location of the centre of the target, and at the height where the atmospheric temperature equals the average brightness temperature of the 20 % coldest pixels in the target.…”
Section: Motion Trackingmentioning
confidence: 99%
“…The target cloud is then identified from the cleaned image (after the removal of noisy structures). In the present study, the target cloud is identified as the cloud that have the highest gradient value and number of pixels (Borde and García-Pereda, 2014) and at the same time should be isolated and persists for some time (at least in the next image). Further, priority is given to that cloud (if more than one cloud satisfies the above criteria) which is at the center of the image.…”
Section: Image Processing and Target Cloud Identificationmentioning
confidence: 99%
“…Any error in the estimation of cloud base height will lead to significant errors in both pixel width and velocity of cloud (Park et al, 2012;Borde and García-Pereda, 2014 and references therein). Since height information is very crucial, a lidar, which provides the cloud information at a resolution of 30 m, is employed in the present study.…”
Section: Estimation Of Cloud Height and Pixel Widthmentioning
confidence: 99%